2016
DOI: 10.1111/joop.12163
|View full text |Cite
|
Sign up to set email alerts
|

Bringing work stress home: The impact of role conflict and role overload on spousal marital satisfaction

Abstract: Many previous studies have explored the possibility that work stressors negatively impact the well-being of an individual's spouse with little success. This study aimed to extend the existing literature by exploring boundary conditions of the relationship including the possibility that political skill and gender modify the relationship between role conflict, role overload, and spousal marital satisfaction. It also suggests that men and women differ in their propensity to cope with different types of stressors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 108 publications
1
27
0
Order By: Relevance
“…This matter was highlighted by previous researchers. For example, Carnes (2017) as well as Hochschild and Manchung (1989) stated that the high level of stress among female employees was due to the competitive demand between the responsibility at home and the workplace. More worrying were the studies by Carnes (2017), Grzywacz, Almeida, and McDonald (2002) as well as Haynes, Eaker, and Feinleib (1983), which showed that working women were prone to exhibit pressure and behavior culminating from stress towards their family members.…”
Section: Problem Statementmentioning
confidence: 99%
“…This matter was highlighted by previous researchers. For example, Carnes (2017) as well as Hochschild and Manchung (1989) stated that the high level of stress among female employees was due to the competitive demand between the responsibility at home and the workplace. More worrying were the studies by Carnes (2017), Grzywacz, Almeida, and McDonald (2002) as well as Haynes, Eaker, and Feinleib (1983), which showed that working women were prone to exhibit pressure and behavior culminating from stress towards their family members.…”
Section: Problem Statementmentioning
confidence: 99%
“…In the stress literature, people often (and implicitly) are depicted as if they were required to face difficulties and stressful circumstances independently of their previous actions. Their agency only appears in their coping efforts, and the quality of coping with these situations influences their quality of life, as well as their health and well-being (Thoits, 2010; Carnes, 2017; Praharso et al, 2017). However, important theoretical work connects stress and coping with self-regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Given the challenges of balancing work with marriage demonstrated by previous research (e.g., Helms et al, 2010;Kim & Dew, 2016;Carnes, 2017;Huffman et al, 2017;Peplinska et al, 2017;Umukoro & Oboh, 2017;Yucel, 2017;Xie et al, 2017) it is logical that individuals in marital dyads have some influence over each other's' behavior in the workplace. Further, Hammond and colleagues (2016) Fiske and Glick's (1995) Ambivalent Sexism Theory asserts that both BS and HS are associated with sexual harassment in the workplace.…”
Section: Rationale/hypothesesmentioning
confidence: 99%
“…In addition, research also suggests that certain skills known for being advantageous in the workplace may also benefit individuals in their home and marital life. For example, one study found that political skill can be used as a coping mechanism to lessen the impact of spillover of work stress to the home and can help men see their own role overload related to work-life balance as less distressful to their wives (Carnes, 2017). Because Ambivalent Sexism Theory (Fiske & Glick, 1995) was born out of interest in investigating sexual harassment in the workplace, the proposed thesis employs this theory to determine how women's close interpersonal relationships affect both their intolerance and reporting of sexual harassment in their workplace.…”
Section: Rationale/hypothesesmentioning
confidence: 99%
See 1 more Smart Citation